PENINGKATAN KEMAMAMPAUN BERPIKIR DAN MENGANALISA MASALAH PADA PEMBELAJARAN IPS SISWA KELAS V SDN KASEPUHAN SEWON BANTUL DENGAN METODE PROBLEM SOLVING - Sari, Maya Kartika (Premiere Educandum, 2013)
This Â research Â is Â served Â to Â describe: Â (1) Â the Â studentsâ Â learning activitiesin problem solving techique; (2) studentsâ courage to poseÂ ideas; (3) studentsâ ability to share ideas in problem solving technique; (4) Â studentsâ Â ability Â in Â having Â the Â critical Â thinking Â in Â solving Â theÂ learning problems. This research covers two cycles, each of which includes Â planning, Â implementing, Â controling, Â and Â reflecting. Â TheÂ subject of the research are 32 fifth graders of SD Negeri KasepuhanÂ Sewon Bantul being taught by problem solving technique to developÂ their critical thinking and problem solving skill of the Social Science subject. The results show that: (1) the studentsâ activity develops from 5 active students in pre research stage to 10 in the first cycle; and it becomes 28 in the second cycle; (2) studentsâ courage to pose ideas develops from 4 courageous students in pre research stage to 15 in the first cycle; and 25 in the second cycle; (3) the ability to share ideas develops from 7 capable students in pre research to 12 in the first cycle, and 26 in the second cycle; (4) the thinking skill develops from 2 skilled students in problem solving in pre research stage to 17 in the first cycle, and 24 in the second cycle. The results of the research recommends that poblem solving technique is efficient in developing studentsâ activities, critical thinking skill and problem solving skill in the Social Science subject for the fifth graders of SD Negeri Kasepuhan Sewon Bantul.Â Key words: Â Studentsâ Â Learning Â Activities, Â Critical Â Thinking Â Skill, Problem Solving